The Impact of Green Financial Policies on Enterprises’ Green Technological Innovation: A Quasi-Natural Experiment Based on China’s Green Finance Reform Pilot Zone - Zhao, Yanling; Chen, Jin (International Journal of Global Economics and Management, 2024)
In this paper, to investigate the impact of green financial policies on corporate green technology innovation, a double difference model is constructed using the data of A-share listed companies from 2017 to 2021. The research results show that the establishment of green financial reform pilot zones greatly promotes enterprise green technology innovation. Meanwhile, through the heterogeneity analysis, it is found that the above conclusion works more significantly on state-owned enterprises. The findings of this paper provide new evidence that green financial policies have a facilitating effect on corporate green technological innovation, and also provide empirical support for the further development of green financial pilot policies.